2019
DOI: 10.1016/j.redox.2019.101186
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 participates in sympathetic hyperactivity Post-MI in the PVN by regulating NF-κB pathway and ROS production

Abstract: Sympathetic nerve hyperactivity is a primary reason for fatal ventricular arrhythmias (VAs) following myocardial infarction (MI). Pro-inflammatory cytokines produced in the paraventricular nucleus (PVN) post-MI are associated with sympathetic overexcitation; however, the precise mechanism needs further investigation. Our aim was to explore the mechanism of toll-like receptor 4 (TLR4) and its downstream molecular pathway in mediating sympathetic activity post-MI within the PVN. A rat MI model was developed via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 57 publications
4
68
0
1
Order By: Relevance
“…For instance, under anaerobic conditions, mitochondrial fission and apoptosis-related circRNA (MFACR) suppresses the uninterrupted expression of miR-652-3p and MTP18 proteins, which leads to the imbalance of ROS, triggers the accumulation of mitochondrial fragments, and then results in apoptotic cell death [100]. ROS is involved in the toll-like receptor 4 (TLR4) and its downstream molecular pathway in mediating sympathetic activity post-MI within the paraventricular nucleus (PVN) [101]. The activation of TLR4 enhances the sympathetic activity after myocardial infarction by activating the microglia NF-κB and ROS in the paraventricular nucleus of the hypothalamus.…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 99%
“…For instance, under anaerobic conditions, mitochondrial fission and apoptosis-related circRNA (MFACR) suppresses the uninterrupted expression of miR-652-3p and MTP18 proteins, which leads to the imbalance of ROS, triggers the accumulation of mitochondrial fragments, and then results in apoptotic cell death [100]. ROS is involved in the toll-like receptor 4 (TLR4) and its downstream molecular pathway in mediating sympathetic activity post-MI within the paraventricular nucleus (PVN) [101]. The activation of TLR4 enhances the sympathetic activity after myocardial infarction by activating the microglia NF-κB and ROS in the paraventricular nucleus of the hypothalamus.…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 99%
“…Sepsis-induced myocardial injury is characterized by neutrophil infiltration which triggers inflammatory response and edema [13]. The protein expressions of toll-like receptor 4 (TLR-4) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) have been shown to be upregulated in myocardial tissues of myocardial injury rats [14]. The results of this study suggest that inflammation in myocardial injury rats may have been due to increased release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 73%
“…Among these candidate signaling pathways, the toll-like receptor (TLR) signaling pathway was identified as the relatively most significantly pathway. Previous studies reported that TLR4/NF-κB signaling cascades contributes to VA under myocardial ischemia condition ( Jiang et al., 2019 ; Wang et al., 2019 ). Our former work demonstrated that TLR4/MyD88/CaMKII signaling pathway contributed to obesity-induced ventricular electrical remodeling ( Shuai et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%